LANGUAGE DYNAMICS IN THE DIGITAL ERA: NAVIGATING INNOVATION AND ADAPTATION (American Journal of Pedagogical and Educational Research, 2023)
This article explores the transformative landscape of language in the era of innovation. Focusing on the dynamic evolution and adaptation of language amidst technological advancements, this study investigates how languages harness new vocabulary, syntax, and communication patterns to encompass emerging concepts. Grounded in linguistic theory, sociolinguistics, and digital communication studies, this research illuminates the profound impact of innovation on language, unveiling the intricate ways in which language shapes and is shaped by the rapidly changing technological landscape.